World Bank Group Engagement in Resource-Rich Developing Countries : The Cases of the Plurinational State of Bolivia, Kazakhstan, Mongolia, and Zambia - Independent Evaluation Group (World Bank, Washington, DC, 2016)
This report by the Independent Evaluation Group (IEG) summarizes the experiences of and draws lessons from the country program evaluations of four natural resource-rich countries: the Plurinational State of Bolivia, Kazakhstan, Mongolia, and Zambia. It concludes that although the challenges identified in these countries are not unique, they manifest themselves with particular intensity in three closely interrelated areas that need to be defined and structured as a coherent strategy: (i) management of revenues from an exhaustible resource; (ii) growth and employment in the non-extractive sectors, and (iii) inclusive growth and reduction of poverty. Overall, looking at the four resource-rich countries in this evaluation, one does not see the World Bank Group as having a consistent framework for engagement, driven by the defining characteristics of these countries—their rich endowment with non-renewable natural resources and dependence on revenues from their exploitation. Each of the four stories evolved in a unique way that depended on how the country teams decided to react to differing country circumstances. The main challenge for the Bank Group in these countries today is how to stay relevant and competitive, as its value proposition is no longer its financial resources, but its knowledge and global experience, which may call for a more modest scope of interventions while keeping the focus on key challenges.